Effect of Inclusion of Garlic (Allium sativum) as Feed Additive on Growth and Carcass Characteristics of Japanese Quail - Bhavani, M. Durga (Indian Journal of Animal Nutrition, 2021)
One hundred and fifty, day-old quail chicks randomly distributed to five dietary treatments each with three replicates of ten quails, were offered broiler quail diets (starter and finisher) to meet the nutrient requirements (ICAR, 2013). During the experiment, dried garlic powder (GP) was included at 0.0% (T1: Control), 0.50% (T2), 1.0% (T3), 1.5% (T4) and 2.0% (T5) level. Results indicated that body weight gain increased significantly (P